Trauma and Resiliency in Grandparent-Headed Multigenerational Families. Issue 2 (April 2015) - Lee, Youjung; Blitz, Lisa V.; Srnka, Miranda
This study explored the experiences of 23 grandparents raising grandchildren to better understand the vulnerability and resiliency of grandparent-headed multigenerational families. Three key themes emerged: (a) family trauma with multigenerational impact, (b) multiple stressors impacting the custodial grandparents, and (c) family resiliency that can promote healing and growth. The discussion highlights complex intersections of trauma and stress, and resiliency and healing. Implications for social work practice include the importance of understanding the nature of trauma and resiliency in clinical interventions to ensure the healthy development of children and older adults. Implications for social work advocacy include the necessity to promote flexible policies that address the needs of grandparent-headed households.